2020
DOI: 10.1155/2020/8862953
|View full text |Cite
|
Sign up to set email alerts
|

What Is the Impact of Depletion of Immunoregulatory Genes on Wound Healing? A Systematic Review of Preclinical Evidence

Abstract: Cytokines and growth factors are known to play an important role in the skin wound closure process; however, in knockout organisms, the levels of these molecules can undergo changes that result in the delay or acceleration of this process. Therefore, we systematically reviewed evidence from preclinical studies about the main immunoregulatory molecules involved in skin repair through the analysis of the main mechanisms involved in the depletion of immunoregulatory genes, and we carried out a critical analysis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 115 publications
(83 reference statements)
0
8
0
Order By: Relevance
“…Murine excisional wound models were the primary animal model used in the studies included in this systematic review about the effects of Brassicaceae on skin edema and wounds (rats and mice, respectively). This is probably because rats and mice have long been the preference for animal models in research in various areas, due to their anatomical, physiological, and especially genetic similarities with humans [ 34 ]. Another important factor is that the greater the uniformity of the animals concerning experimental, environmental, and genetic variables, the smaller the sample size of animals needed to develop the research [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Murine excisional wound models were the primary animal model used in the studies included in this systematic review about the effects of Brassicaceae on skin edema and wounds (rats and mice, respectively). This is probably because rats and mice have long been the preference for animal models in research in various areas, due to their anatomical, physiological, and especially genetic similarities with humans [ 34 ]. Another important factor is that the greater the uniformity of the animals concerning experimental, environmental, and genetic variables, the smaller the sample size of animals needed to develop the research [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, females are more sensitive to acute oral toxicity, as well as dermal toxicity, than males [ 14 ]. The age groups of the animals were similar, which is an important feature for studies evaluating wound healing and even intrinsically in studies of the inflammatory process, since aging rats influence the formation of new vessels, wound closure, re-epithelialization, and the resolution of the inflammatory process [ 34 ], due to the activity of enzymes that break down with aging [ 37 ]. Excisional wounds were predominant, although the number and size of wounds were variable.…”
Section: Discussionmentioning
confidence: 99%
“…Most notably, paracrine interactions with PFMs induced a $10-fold increase in IL6 expression in THP-1 macrophages and a corresponding >10-fold increase in IL-6 protein levels in the shared conditioned media (Figure 4). Interactions between IL-6, TNF and TGFβ-1 have been demonstrated in wound healing and fibrosis development, [47][48][49] so it is feasible that similar interactions contribute to DD pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Most of our knowledge regarding the temporal and spatial variations of cytokines in wound healing derives from acute surgical wounds [ 23 , 24 , 25 ]. This knowledge has been supplemented with wound healing studies in knock-out mice models that have convincingly shown that deficiencies of cytokines severely impair wound healing [ 26 , 27 , 28 , 29 ], which underscores the importance of cytokines in normal wound healing.…”
Section: Introductionmentioning
confidence: 99%